Deep Core Stability Exercise Along with Kinesio Taping Therapy Techniques for Diastasis Recti Abdominis : Life Sciences- Physiotherapy - Muthulakshmi, K.; Thirulogachandar, G.; Saravanan, V.; Priyadharshini, P.; Saraswathi, K.; Sowmiya, P.; Sivasakthi, M. (International Journal of Life Science and Pharma Research, 2023)
Diastasis recti abdominis (DRA) has been defined as an impairment characterized by the split of the rectus abdominismuscle along with the linea Alba. Diastasis Rectus Abdominis Muscle is familiar during pregnancy and later pregnancy and hasbeen connected to lumbopelvic stability and pelvic floor weakness. The study aims to find the effect of deep core stabilityexercise and kinesio-taping therapy techniques in diastasis recti. This is an experimental design with pre and post-comparativestudy. The study setting is at the Faculty of Physiotherapy ACS Medical College and Hospital 30 samples were selected, andintervention was carried out for about 4 weeks. If diastasis recti abdominis was present at 8 weeks postpartum, either vaginaldelivery or cesarean section were options. Less than 8 weeks after giving birth, the following ailments were excluded:respiratory illnesses, sensory defects, neurological disorders, hypertension, diabetes mellitus, heart conditions, abdominalsurgeries, vaginal hemorrhage, skin conditions, pregnancy, obesity, and neoplastic diseases. In Group-A, 15 subjects receiveddeep core stability exercises and Kinesio taping, while Group-B, 15 received Traditional abdominal exercises. The outcome toolswere the digital nylon caliper and finger breath. On comparing the Pretest and Posttest within Group A & Group B on DigitalNylon Caliper (Above Umbilicus and below Umbilicus) score & finger Breadths (Above Umbilicus and below Umbilicus) scoreshows a significant difference in the mean values at P ≤ 0.05. This study concluded that deep core stability exercise and kinesiotaping therapy techniques effectively reduce diastasis recti in postpartum women; they help restore postpartum abdominalefficiency. These exercises could be effective in narrowing the inter-recti distance. The result shows that deep core stabilityexercise and kinesio taping therapy techniques significantly reduce diastasis recti.